Certification Problem
Input (COPS 37)
We consider the TRS containing the following rules:
f(a,x) |
→ |
f(a,g(x)) |
(1) |
a |
→ |
b |
(2) |
g(x) |
→ |
x |
(3) |
The underlying signature is as follows:
{f/2, a/0, g/1, b/0}Property / Task
Prove or disprove confluence.Answer / Result
Yes.Proof (by csi @ CoCo 2023)
1 Redundant Rules Transformation
To prove that the TRS is (non-)confluent, we show (non-)confluence of the following
modified system:
g(x) |
→ |
x |
(3) |
a |
→ |
b |
(2) |
f(a,x) |
→ |
f(a,g(x)) |
(1) |
f(a,x) |
→ |
f(a,x) |
(4) |
f(a,x) |
→ |
f(b,g(x)) |
(5) |
f(a,x) |
→ |
f(a,g(g(x))) |
(6) |
All redundant rules that were added or removed can be
simulated in 2 steps
.
1.1 Decreasing Diagrams
1.1.2 Rule Labeling
Confluence is proven, because all critical peaks can be joined decreasingly
using the following rule labeling function (rules that are not shown have label 0).
-
↦ 0
-
↦ 1
-
↦ 0
-
↦ 0
-
↦ 2
-
f(a,x) |
→ |
f(a,g(g(x))) |
(6) |
↦ 3
The critical pairs can be joined as follows. Here,
↔ is always chosen as an appropriate rewrite relation which
is automatically inferred by the certifier.
-
The critical peak s = f(b,x)←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(b,x) ↔ f(a,x) ↔
t
-
The critical peak s = f(b,x)←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(b,x) ↔ f(b,g(x)) ↔
t
-
The critical peak s = f(b,x)←→ε f(a,x) = t can be joined as follows.
s
↔ f(b,x) ↔
t
-
The critical peak s = f(b,x)←→ε f(b,g(x)) = t can be joined as follows.
s
↔ f(b,x) ↔
t
-
The critical peak s = f(b,x)←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(b,x) ↔ f(a,x) ↔ f(a,g(x)) ↔
t
-
The critical peak s = f(b,x)←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(b,x) ↔ f(b,g(x)) ↔ f(a,g(x)) ↔
t
-
The critical peak s = f(b,x)←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(b,x) ↔ f(b,g(x)) ↔ f(b,g(g(x))) ↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,x) = t can be joined as follows.
s
↔ f(a,g(x)) ↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,x) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,x) = t can be joined as follows.
s
↔ f(b,g(x)) ↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,x) = t can be joined as follows.
s
↔ f(a,g(g(x))) ↔
t
-
The critical peak s = f(a,g(x))←→ε f(b,g(x)) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(a,g(x)) ↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(b,g(g(x))) ↔
t
-
The critical peak s = f(a,g(x))←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(a,g(g(g(x)))) ↔
t
-
The critical peak s = f(a,x)←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(a,x) ↔
t
-
The critical peak s = f(a,x)←→ε f(a,g(x)) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(a,x)←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(b,g(x)) ↔
t
-
The critical peak s = f(a,x)←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(a,g(g(x))) ↔
t
-
The critical peak s = f(a,x)←→ε f(b,g(x)) = t can be joined as follows.
s
↔ f(b,x) ↔
t
-
The critical peak s = f(a,x)←→ε f(b,g(x)) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(a,x)←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(a,g(x)) ↔
t
-
The critical peak s = f(a,x)←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(b,g(x))←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(b,g(x)) ↔
t
-
The critical peak s = f(b,g(x))←→ε f(a,x) = t can be joined as follows.
s
↔ f(b,g(x)) ↔
t
-
The critical peak s = f(b,g(x))←→ε f(a,x) = t can be joined as follows.
s
↔ f(b,x) ↔
t
-
The critical peak s = f(b,g(x))←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(b,g(x)) ↔ f(a,g(x)) ↔
t
-
The critical peak s = f(b,g(x))←→ε f(a,g(g(x))) = t can be joined as follows.
s
↔ f(b,g(x)) ↔ f(b,g(g(x))) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(a,g(g(x))) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(a,g(x)) = t can be joined as follows.
s
↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(b,g(g(x))) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(a,g(x)) = t can be joined as follows.
s
↔ f(a,g(g(g(x)))) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(a,x) = t can be joined as follows.
s
↔ f(a,g(g(x))) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(a,x) = t can be joined as follows.
s
↔ f(a,g(x)) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(b,g(x)) = t can be joined as follows.
s
↔ f(a,g(x)) ↔
t
-
The critical peak s = f(a,g(g(x)))←→ε f(b,g(x)) = t can be joined as follows.
s
↔ f(b,g(g(x))) ↔
t
/>